Fabrication And Characterization Of Normoxic Polymer Gel Dosimeter By Using Raman Spectroscopy At Low X-Ray Energies - Rozlan, Aifa Aflrah (2012)
Polymer gel dosimeters are fabricated from radiation sensitive chemicals which, upon irradiation, polymerize as a function of the absorbed radiation dose. Two types of normoxic polymer gel dosimeters were fabricated, which is PHEAG (polyhydroxyethyl acrylate) and PHEMAG (polyhydroxyethyl methacrylate) gel dosimeters. These polymer were fabricated by using gelatin, N' N-methylene-bisacrylamide (BIS), ascorbic acid (AA), deionized water and 2-hydroxyethyl acrylate (HEA) for PHEAG and 2-hydroxyethyl methacrylate for PHEMAG. The ability of AA to bind oxygen in the gel solution was investigated by using an oxygen dissolve meter. The concentrations of AA used are 5, 10, 15 and 35 mM and each concentration was applied to each batch of PHEAG and PHEMAG. The sensitivity of PHEAG and PHEMAG towards low X-ray energy was investigated. The structural changes of the monomeric components in PHEAG and PHEMAG after irradiation were analyzed using Raman spectroscopy.